Feiticeiros Negros no Grão-Pará (1755-1772) - (:unkn) unknown (Universidade Federal do Amazonas, 2014)
In the mid of the 18th century, the magical practices of blacks and creoles people slaves in Grão Pará were present in daily life. These practitioners, whom were called mandingueiros in Portugal and Africa and in Brazil colony were associated with sorcerers, reframed their practices, giving them new meanings. Under the Regiment of 1.640, inquisitorial officials were send to the Grão-Pará State, among them Giraldo José de Abranches, as the one chosen to impose ̶ even that late and with less force if compared to other parts of the State of Brazil ̶ a moral control, determining the religious conduct to be followed by the new Christians and over those who had any type of suspicious behavior of heresy. Slaves taken as witches gave heed to every kind of requests, even for benefits or for harm, assigning letters to its beneficiaries or customers. They made the most various kinds of spells, such as: loving; to cure diseases and to make ill; to undo spells; tidying up husbands and lovers; to guess loss and theft, superstitions, not desired pregnancy, among others.
Keywords: Feiticeiros; Negros; Escravos; Inquisição; CIÊNCIAS HUMANAS: HISTÓRIA